Lesser Canna Leafroller, Geshna cannalis (Quaintance) (Insecta: Lepidoptera: Pyralidae) - Heather J. McAuslane (EDIS)
The lesser canna leafroller, Geshna cannalis (Quaintance), can be a serious pest of ornamental canna, Canna spp., in Florida. It is one of two leaf-rolling lepidopteran species found infesting canna, the other one being the larger and more voracious larger canna leafroller, Calpodes ethlius (Stoll). Cannas may be infested with both species simultaneously.  This document is EENY-133, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2000.